The Effectiveness of Parenting Cooperation Models for Parents and Teachers in Developing Social and Emotional Early Childhood - Syuraini Syuraini (Universitas Negeri Padang, 2020)
Maybe some parents still think that children's education is a normal thing and naturally children will become smart. Some still believe that according to the age of the child will develop with the help of teachers at school without having to work hard at home. This is happening right now for parents who don't understand the importance of the role of parents in children's education. In this study a parenting collaboration model was developed using development research. In this research, the effectiveness and practicality of the model are very real where the presence and enthusiasm of parents is very high to participate in parenting activities. Principals and teachers have very positive responses to the parenting program. It is recommended that teachers always make and implement parenting programs with parents from the beginning of planning to evaluating programs.Keywords: Parenting Cooperation, Social Development, Emotion Development, Early Childhood